Give Me the Facts or Make Me Feel: How to Effectively Persuade Consumers to Act on a Collective Goal - Jin, Liyin; Wang, Yajin; Zhang, Ying (Journal of Marketing, 2023)
This research explores how marketers can best persuade consumers to act in a collective goal context, such as giving to a donation campaign or signing a petition. The authors examine whether consumers respond differently to fact-based versus affect-based persuasive messages at different stages of a collective campaign. Seven studies demonstrate that the relative impact of fact-based versus affect-based appeals changes with varying distance to the completion of the collective goal. Whereas a fact-based message better persuades consumers to support a collective goal when the distance to completion is large (i.e., far from completion), an affect-based message better persuades consumers to support the goal when the distance to completion is small (i.e., near completion). This enhanced persuasion occurs because the psychological state triggered by the remaining distance matches the message type and, in turn, encourages deeper processing of the appeal.